ERP: an investigation into the decision between buying commercial package and developing internally - Azanha, Adrialdo (2017)
The contemporary scenario demands from the organizations a greater concern in terms of making the management of their activities more effective, in order to increase their competitiveness through cost reduction and operational efficiency. In this sense, the systems of enterprise management (ERP) appear as a solution to this conjuncture. Typically, an ERP is procured in the form of a ready package; however, some companies choose to develop it internally, influenced by the complexity of implementing these market software solutions. Thus, the objective of this work is to analyze the characteristics of a commercial ERP and a locally developed ERP, drawing a comparison between these two approaches to understand the best solution to help processes in large companies. The methodology used was the exploratory qualitative research, through a case study in a large company of the industrial sector of heavy equipment, which promoted the implementation of ERP in both ways throughout its existence. It has been found that adopting the internally developed system is easier and better meets the requirements of the company. However, the managers of the organization considered that the commercial ERP is more beneficial, due to the possibility of greater integration between the subsidiaries and the other companies of the supply chain, a relevant point in the company strategy.